From Voluntarism to Regulation: A Study on Ownership, Economic Performance and Corporate Environmental Information Disclosure in China - Meng, X. H.; Zeng, Saixing; Tam, Chiming (2013)
This article examines whether economic performance could affect EID and how the relationship is determined by the form of ownership from voluntarism to regulation under the current Chinese context. In this study, our empirical results show that the relationship between firms’ performance and EID is complex and the interactive impact of ownership and economic performance on EID significantly varies from voluntary disclosure to mandatory disclosure. This study provides a more comprehensive understanding of the motivations in corporate EID. The performance–impression theory can be used to explain the disclosure behaviors during the period of voluntary disclosure, while the pressure–legitimacy theory can be used during the period of mandatory disclosure. The finding suggests that when evaluating corporate EID associated with economic performance in emerging economies such as China, it needs to be cautious, as which tends to vary with the form of ownership and whether there is any mandatory regulation in place.
Keywords: Voluntarism; Regulation; Ownership; Environmental information disclosure (EID); Economic Performance